2021
DOI: 10.1055/s-0041-1734029
|View full text |Cite
|
Sign up to set email alerts
|

Globalization in Pediatric Surgical Training: The Benefit of an International Fellowship in a Low-to-Middle–Income Country Academic Hospital

Abstract: Objective A relative oversupply of pediatric surgeons led to increasing difficulties in surgical training in high-income countries (HIC), popularizing international fellowships in low-to-middle–income countries (LMIC). The aim of this study was to evaluate the benefit of an international fellowship in an LMIC for the training of pediatric surgery trainees from HICs. Methods We retrospectively reviewed and compared the prospectively maintained surgical logbooks of international pediatric surgical trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Zanini et al in 2021 demonstrated that of the European surgical trainees (both pre and postqualification) who visited the DPS, operative experience was higher in South Africa for all general and index pediatric surgical cases than in their country of origin, except for minimally invasive surgery. 31 The results of this study demonstrate that resources are available for the selected OReCS strategies for quality improvement in the subspecialty units of the DPS.…”
Section: Yearmentioning
confidence: 71%
See 1 more Smart Citation
“…Zanini et al in 2021 demonstrated that of the European surgical trainees (both pre and postqualification) who visited the DPS, operative experience was higher in South Africa for all general and index pediatric surgical cases than in their country of origin, except for minimally invasive surgery. 31 The results of this study demonstrate that resources are available for the selected OReCS strategies for quality improvement in the subspecialty units of the DPS.…”
Section: Yearmentioning
confidence: 71%
“…The contribution of the visiting trainees and surgeons to the workforce, surgeries performed, and research is regarded as invaluable by the DPS. Zanini et al in 2021 demonstrated that of the European surgical trainees (both pre and postqualification) who visited the DPS, operative experience was higher in South Africa for all general and index pediatric surgical cases than in their country of origin, except for minimally invasive surgery 31 …”
Section: Discussionmentioning
confidence: 99%